KEABSAHAN PENGESAHAN PERJANJIAN PERDAMAIAN PADA PERKARA PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (Studi Putusan Nomor: 24/Pdt.Sus-PKPU/2021/PN Niaga Jkt.Pst.) - Jenny Lim; Ariawan Ariawan (Fakultas Hukum Universitas Tarumanagara, 2021)
In the world of trade and commerce, there are certain times when the company experiences financial difficulties, so that the company/debtor has difficulty or is no longer able to pay its debts. Considering that Bankruptcy is an Ultimatum Remedium, a regulations regarding Postponement of Debt Payment Obligations (PKPU) is enacted. In PKPU, there is a peace plan known as peace agreements. This opportunity is given to debtors to save the company from bankruptcy, so that it can settle its debts. For the research, The author examines using normative juridical research methods. As the results of the research, it can be concluded that, the ratification of a peace agreement must meet the requirements and procedures for ratification of a peace agreement as regulated in the bankruptcy law and PKPU. In offering a peace agreement it must be in a good faith, the benchmark of good faith is when The agreement is based on pretium iustum which refers to reason and equity which implies a balance between losses and gains for both parties in the contract (just price)